2019
DOI: 10.1093/ejo/cjz086
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of skeletal anchorage and tooth-borne maxillary protraction followed by fixed appliance in Class III malocclusion

Abstract: Summary Objectives The purpose of this study was to compare the results of skeletal anchorage (SAMP) and tooth- borne (TBMP) maxillary protraction followed by fixed appliance in growing skeletal Class III patients. Materials and methods Patients treated with maxillary protraction were selected and classified into two groups (SAMP: n = 19, mean age = 11.19 years; TBMP: n = 27, mean age = 11.21… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
17
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 28 publications
3
17
1
Order By: Relevance
“…In parallel with the findings of the literature, 2,33‐39 an increase in dentoalveolar parameters, protrusion in the upper incisors, retrusion in the lower incisors and, accordingly, an increase in overjet was observed in all three groups. Although there was no direct support from the upper incisors in all the groups, protrusion occurred in the upper incisors as a result of mesialization of the upper teeth from the protraction force in the RME and modified Alt‐RAMEC groups, which received support from the posterior teeth.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…In parallel with the findings of the literature, 2,33‐39 an increase in dentoalveolar parameters, protrusion in the upper incisors, retrusion in the lower incisors and, accordingly, an increase in overjet was observed in all three groups. Although there was no direct support from the upper incisors in all the groups, protrusion occurred in the upper incisors as a result of mesialization of the upper teeth from the protraction force in the RME and modified Alt‐RAMEC groups, which received support from the posterior teeth.…”
Section: Discussionsupporting
confidence: 88%
“…Sar et al reported a 1.63° counterclockwise rotation in the maxilla with a conventional face mask and a 0.92° rotation from the miniplates in the facemask group 23 . Lee et al reported a 0.54° counterclockwise rotation in the maxilla with a conventional face mask, and a 0.73° rotation from the miniplates in the facemask group 36 . While the most rotation among the three groups in our study was in the RME group (−2.69°), the least rotation was found in the skeletal anchorage group (−0.31°).…”
Section: Discussioncontrasting
confidence: 51%
See 3 more Smart Citations